Voices of Departure: A Cognitive Discourse Analysis of Catholic Exit Stories - Berdowicz, Ewelina (Człowiek i Społeczeństwo, 2025)
This paper explores the narratives of former Polish Catholics through the lens of Cognitive Discourse Analysis (CODA), focusing on how individuals linguistically reconstruct their exit from the Church. Based on in-depth, unstructured interviews, the study investigates how deconverts conceptualize their religious past, moments of disillusionment, and post-religious identity. Particular attention is paid to metaphor, evaluative language, and conceptual oppositions which serve as discursive tools for expressing rupture, resistance, and recovery. Rather than reducing disaffiliation to doctrinal disagreement, the study examines how shifts in personal meaning-making are shaped by emotional, cognitive, and cultural factors. The analysis reveals that language not only reflects but also performs the act of deconversion, allowing individuals to reframe past experiences and reclaim interpretive authority. These “voices of departure” illuminate both individual trajectories and broader trends of religious disengagement in contemporary Poland.